Identification of Paleovolcanic Centers in the Bima District, East Sumbawa Island (Indonesia) as Guidance for Future Exploration of Cu-Au Deposits - Habib, Juhair Al; Setijadji, Lucas Donny; Maryono, Adi; Rompo, Iryanto (Geological Engineering Department Universitas Gadjah Mada, 2024)
The formation of Cu-Au mineralization, such as porphyry and epithermal deposits, is strongly associated with volcanic processes in specific tectonic settings, such as subduction zones. The identification of the presence of ancient volcanoes is one of the important steps to finding mineral deposits. This study aims to identify the presence of ancient volcanoes in the Bima District, eastern part of Sumbawa Island, as a step toward determining the potential indication of Cu-Au mineralization. The methods used in this research consist of a literature study, image analysis and remote sensing, field survey and data collection, and petrographic analysis. Image analysis using DEMNAS (Digital Elevation Model), including texture and pattern analysis using the concept of volcanic anatomy, aims to identify the remaining forms of ancient volcanoes. Field surveys and data collection include volcano geomorphology, lithology and sampling, and also geological structures. Petrographic analysis is conducted to qualitatively characterize the texture, structure, and mineralogy of volcanic rocks. The identification results show that there are at least ten volcanoes (crown) identified through image analysis, namely Doro Mbangga, Doro Baku, Doro Donggo Masa, Doro Rompo, Doro Sape, Doro Kowo, Doro Jia, Doro Sambori, Doro Mangge, and Doro Lambu. Each of these volcanoes has one or more eruption center (hummock). The eruption center identified in the central, proximal, to distal facies of the volcano, even superimposing one volcano product with another, and spread around 80-90% in the study area. The volcanic facies in the study area are characterized by the central part being composed of lithologies such as intrusive rocks, lava, and diatreme breccia, while the proximal and distal facies are composed of breccia, volcanic breccia, and tuff. Hydrothermal alteration zones are identified in the central and proximal facies of the volcano. These alterations were associated with the presence of eruption centers, where the abundance of eruption centers means that hydrothermal alterations are particularly well developed and pervasively formed. Identified argillic and advanced argillic alteration associated with stockworks forming a lithocap environment. In addition, the presence of intrusive rocks such as diorite and dacite with chloritic and sericitic alteration in the central facies of Doro Baku can be associated with the presence of deposits such as porphyry and epithermal, so the identification of ancient volcanic eruption centers in the Bima district has implications for the potential discovery of Cu-Au mineralization, such as porphyry and epithermal deposits.